1983
DOI: 10.1002/jso.2930240118
|View full text |Cite
|
Sign up to set email alerts
|

In vitro chemotherapy sensitivity patterns of human colon carcinoma continuous cell lines

Abstract: The cells obtained from four established human colon carcinoma cell lines were cultured in soft agar in the presence of eight chemotherapeutic agents that have been used clinically in patients with metastatic colorectal carcinoma. 5-Fluorouracil, mitomycin C, adriamycin, and cis-platinum were highly cytotoxic in vitro at the concentrations employed. These findings were in marked contrast to in vitro chemotherapy sensitivity patterns previously reported by us for a large series of primary human colorectal carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…), and cytosine arabinoside (Cytosar-U, 1.0, 0.1 and 0.01 pg/ml, Upjohn Co., Kalamazoo, Mich.). These concentrations had been utilized in previous studies by other authors [8,9] or spanned the range of reported achievable in vivo serum or plasma concentrations [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Drugsmentioning
confidence: 99%
“…), and cytosine arabinoside (Cytosar-U, 1.0, 0.1 and 0.01 pg/ml, Upjohn Co., Kalamazoo, Mich.). These concentrations had been utilized in previous studies by other authors [8,9] or spanned the range of reported achievable in vivo serum or plasma concentrations [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Drugsmentioning
confidence: 99%